SUSTAINABLE TERRITORIAL DEVELOPMENT STRATEGIE - Aurel-Gabriel, SIMIONESCU; Mariana-Carmelia, DRAGOMIR (Strategii Manageriale)
The development of the different regions of Europe throughout history has known different phases and evolutions according to the conditions which they have gone through. The aim of this article is to present an analysis of European regions depending on three essential elements of a unitary development including: concentration of resources, connecting regions and cooperation, highlighting a number of directions for a sustainable development.From this perspective in the EU financial period 2014-2020, national targets and regional funding should take into account varied issues, focusing on the structure and the concentration of population for the necessary conditions of housing and living (infrastructure, utilities, public services, education, health and social services) to be satisfied.